In search of a trade mark. Search practices and bureaucratic poetics. Issue 2 (2nd April 2016) - Bellido, Jose; Kang, Hyo Yoon
ABSTRACT: Trade marks have been understood as quintessential 'bureaucratic properties'. This article suggests that the making of trade marks has been historically influenced by bureaucratic practices of search and classification, which in turn were affected by the possibilities and limits of spatial organisation and technological means of access and storage. It shows how the organisation of access and retrieval did not only condition the possibility of conceiving new trade marks, but also served to delineate their intangible proprietary boundaries. Thereby they framed the very meaning of a trade mark. By advancing a historical analysis that is sensitive to shifts, both in actual materiality and in the administrative routines of trade mark law, the article highlights the legal form of trade mark as inherently social and materially shaped. We propose a historical understanding of trade mark law that regards legal practice and bureaucratic routines as being co-constitutive of the very legal object itself.